PENGARUH MODEL LATIHAN KIDS TSU CHU TERHADAP KETERAMPILAN BERMAIN SEPAKBOLA CLUB PUTRA MAYANA KU-20 KADUGEDE - Boby Agustan; Dany Ahmad Prasetyo; Ramdhani Rahman (STKIP Muhammadiyah Kuningan, 2022)
ABSTRACT Dany Ahmad Prasetyo (NIM: 182223031), with the title